Extraction Optimization of Polysaccharides From Corn Silk and Their Antioxidant Activities in vitro and in vivo - Zhang, Liang; Yang, Yang; Wang, Zhanyong (Frontiers in Pharmacology, 2021)
The extraction of corn silk polysaccharidespolysaccharides in corn silk (CSP) was optimized by response surface methodology based on a Box–Behnken design. Three independent variables, namely, temperature, liquid-to-solid ratio and extraction timeper extraction time, were investigated. Experimental data were fitted to a second-order polynomial, and the optimum extraction conditions were as follows: temperature of 88 °C, liquid-to-solid ratio of 21.5 mL/g, and extraction timeper extraction time of 1.87 h. Under these conditions, the experimental yield of the extracted polysaccharides was 4.33% ± 0.08% (dry wight), which fit well with the predicted value. In vitro antioxidant assay proved the high scavenging activities toward 1,1-diphenyl-2-picrylhydrazyl radicals, superoxide anions, and hydroxyls and good reducing power of CSP. Meanwhile, in vivo analysis showed that CSP significantly increased the activity of superoxide dismutase and glutathione peroxidaseantioxidant enzymes. andIt also reduced the levels of malondialdehyde in the serum and liver of aging mice induced with D-galactose. This study demonstrated that CSP exhibits strong high antioxidant activities in vitro and in vivo and could can be exploitedexplored as a possiblepotential antioxidants for health functional food and medicine.